Cysticercosis in Madagascar - Jean-François Carod; Pierre Dorny (Journal of Infection in Developing Countries)
Introduction: Cysticercosis (CC) is the most common parasitic disease of the central nervous system. It is endemic in most developing countries where pigs are raised and consumed. An overview of all available data of this parasite in Madagascar is lacking.